1991
DOI: 10.1172/jci115491
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic protoporphyria in the house mouse. A recessive inherited ferrochelatase deficiency with anemia, photosensitivity, and liver disease.

Abstract: A viable autosomal recessive mutation (named fch, or ferrochelatase deficiency) causing jaundice and anemia in mice arose in a mutagenesis experiment using ethylnitrosourea. Homozygotes (fch/fch) display a hemolytic anemia, photosensitivity, cholestasis, and severe hepatic dysfunction. Protoporphyrin is found at high concentration in erythrocytes, serum, and liver. Ferrochelatase activity in various tissues is 2.7-6.3% of normal. Heterozygotes (+/fch) are not anemic and have normal liver function; they are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 17 publications
4
105
0
Order By: Relevance
“…38 In the murine EPP model, the Fech m1Pas /Fech m1Pas mutant mouse (BALB/cJ), homozygous deficient animals exhibit hemolytic anemia and increased protoporphyrin levels inducing photosensitivity, cholestasis, and severe hepatic dysfunc- tion. 18 Hepatic defects represent a major and constant feature: onset of hepatomegaly is very early. Both cutaneous photosensitivity and liver impairment are the result of the accumulation of mostly erythrocyte-derived porphyrins.…”
Section: Discussionmentioning
confidence: 99%
“…38 In the murine EPP model, the Fech m1Pas /Fech m1Pas mutant mouse (BALB/cJ), homozygous deficient animals exhibit hemolytic anemia and increased protoporphyrin levels inducing photosensitivity, cholestasis, and severe hepatic dysfunc- tion. 18 Hepatic defects represent a major and constant feature: onset of hepatomegaly is very early. Both cutaneous photosensitivity and liver impairment are the result of the accumulation of mostly erythrocyte-derived porphyrins.…”
Section: Discussionmentioning
confidence: 99%
“…The BALB/c Fech m1Pas mouse strain was obtained from the The Jackson Laboratory (Bar Harbor, ME). The Fech m1Pas mutant contains a point mutation in the ferrochelatase gene (Tutois et al, 1991;Davies et al, 2005). Mice were bred by homozygous mating and maintained in a negative pressure isolator at 21°C under reduced light to prevent skin lesions.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical studies demonstrate that the mutant shows 10 to 15% ferrochelatase activity of control level, although immunochemical experiments revealed that a normal size of ferrochelatase (-40 kDa) is present in normal levels (Bloomer et al 1987). Very recently, a viable autosomal recessive mutation causing jaundice and anemia in mice arose by a mutagenesis experiment using ethylnitrosourea (Tutois et al 1991). The mutant mice exhibits ferrochelatase activity at 2.7, 6.3 and 3.3% of normal levels in kidney, liver and spleen, respectively.…”
Section: Molecular Basis Of Erythropoietic Protoporphyriamentioning
confidence: 99%